Where Do Action Goals Come from? Evidence for Spontaneous Action–Effect Binding in Infants - Verschoor, Stephan Alexander; Weidema, Maaike; Biro, Szilvia; Hommel, Bernhard (Frontiers in Psychology, 2010)
One of the great questions in psychology concerns how we develop to become intentional agents. Ideomotor theory suggests that intentional actions depend on, and emerge from the automatic acquisition of bidirectional action-effect associations: perceiving an action-effect sequence creates an integrated representation that can be employed for action control in the opposite order, selecting an action by anticipating its effect. We provide first evidence for the spontaneous acquisition of bidirectional action-effect associations in 9- 12- and 18-month-olds, suggesting that the mechanism underlying action-effect integration is in place at the latest around 9-months-old.